Asymptomatic primary tumour in incurable metastatic colorectal cancer: is there a role for surgical resection prior to systematic therapy or not? - Narimantas E. Samalavicius; Audrius Dulskas; Edita Baltruskeviciene; Giedre Smailyte; Marija Skuciene; Rasa Mikelenaite; Rasa Venslovaite; Eduardas Aleknavicius; Almantas Samalavicius; Raimundas Lunevicius (Videosurgery and Other Miniinvasive Techniques)
Introduction: The role of the resection of asymptomatic primary colorectal cancer in patients with incurable disease is questionable. Aim: To evaluate the impact of the resection of asymptomatic primary tumour on overall survival in patients with unresectable distant metastases. Material and methods : Patients treated in the National Cancer Institute, Lithuania, in the period 2008–2012, were selected retrospectively. The main inclusion criteria were: metastatic colorectal cancer (mCRC), endoscopically and histologically confirmed adenocarcinoma, without any symptoms for urgent operation, and at least one cycle of palliative chemotherapy administered. Information on patients’ age, gender, tumour histology, localization of the tumour, regional lymph node involvement, number of metastatic sites, surgery and systemic treatment was collected prospectively. Eligible patients for the study were divided into two groups according to the initial treatment – surgery (patients who underwent primary tumour resection) and chemotherapy (patients who received chemotherapy without surgery). The impact of initial treatment strategy, tumour size and site, regional lymph nodes, grade of differentiation of adenocarcinoma and application of biotherapy on overall cumulative survival was estimated using the Kaplan-Meier method. To compare survival between groups the log-rank test was used. Cox regression analysis was employed to assess the effects of variables on patient survival. Results: The study group consisted of 183 patients: 103 men and 80 women. The median age was 66 years (range: 37–91). There were no notable imbalances with regard to age, gender, number of metastatic sites, metastases (such as pulmonary, peritoneal, liver, metastases into non-regional lymph nodes and other metastases), the number of received cycles of chemotherapy, first line chemotherapy type or biological therapy. Only 27 (14.8%) patients received biological therapy and the majority of them (n = 25, 92.6%) were treated with bevacizumab. For surgically treated patients 1-year survival was 71.2% (95% CI: 62.1–78.5) and 5-year survival was 4.0% (95% CI: 1.0–10.5). In the chemotherapy group, survival rates were lower – 43.9% (95% CI: 31.4–55.7) and 1.7% (95% CI: 0.1–8.1), respectively. Better survival rates were in the palliative surgery group. Multivariate analysis using the Cox proportional hazards model revealed that the initial palliative surgery and the application of biological therapy were statistically significant independent prognostic factors for survival. Conclusions : Our findings suggest that palliative resectional surgery for the primary tumour in patients with incurable mCRC improves survival. Of course, one can argue that patients in the surgery group were “less problematic”. Prospective randomized trials are needed to delineate precisely the role of palliative surgery of the primary tumour in these patients.